Recent progress and emerging technologies in geothermal energy utilization for sustainable building heating and cooling: a focus on smart system integration and enhanced efficiency solutions - Eze, Val Hyginus Udoka; Eze, Esther Chidinma; Alaneme, George Uwadiegwu; Bubu, Pius Erheyovwe (Frontiers in Built Environment, 2025)
Geothermal energy has gained prominence as a sustainable solution for heating and cooling, driven by technological innovations and the growing global demand for energy efficiency. Geothermal systems, particularly ground-source heat pumps (GSHPs), exhibit high energy efficiency, with coefficients of performance (COP) ranging from 3.5 to 6.0, while deep geothermal systems operate at temperatures of 50°C–200°C, supporting both power generation and large-scale heating applications. Enhanced Geothermal Systems (EGS) use hydraulic, chemical, and thermal stimulation to extract heat from low-permeability formations, significantly expanding the applicability of geothermal resources beyond traditional hotspots. Geothermal heat pumps are capable of achieving energy efficiency levels of 300%–600%, reducing CO2 emissions by 50%–70% when compared to fossil fuel-based HVAC systems. However, installation costs for GSHPs range from $2,500 to $5,000 per kW, while deep geothermal systems require higher capital investments. Despite these initial costs, operational expenses remain competitive at $0.01–$0.03 per kWh, and geothermal plants exhibit high-capacity factors of 70%–90%, outperforming solar (20%–30%) and wind (30%–50%) in terms of energy production consistency. The return on investment (ROI) for geothermal systems typically occurs within 5–15 years, depending on location and system scale. The integration of smart technologies, such as artificial intelligence (AI), machine learning (ML), and the Internet of Things (IoT), further enhances the efficiency of geothermal energy systems by enabling real-time monitoring, predictive maintenance, and load forecasting, optimizing overall performance and longevity. Hybrid systems, combining geothermal energy with solar, wind, and thermal energy storage, improve grid stability and further enhance energy efficiency. Despite challenges such as geological constraints, high initial costs, and regulatory barriers, policy frameworks and government incentives play a vital role in promoting the expansion of geothermal energy. The global geothermal capacity surpassed 16 GW in 2023 and is projected to exceed 24 GW by 2030, with significant deployments in countries like the U.S., Indonesia, Kenya, the Philippines, and Turkey. Notable geothermal projects include the Olkaria Geothermal Power Plant (800 MW, Kenya), The Geysers (1.5 GW, United States), Hellisheidi (303 MW electricity, 400 MW thermal, Iceland), and the Yangbajain Geothermal Power Station in China (25.5 MW and 100 GWh annual generation). As nations aim for carbon neutrality and energy security, geothermal energy is poised to play a crucial role in achieving sustainable energy transitions and mitigating climate change.